MRI of the arterial wall in resistant hypertension associated with type 2 diabetes mellitus - Nadezhda I. Ryumshina; Alla Y. Falkovskaya; Anna M. Gusakova; Victor F. Mordovin; Vladimir Y. Usov (Сахарный диабет)
BACKGROUND: Damage of arterial walls in diabetes mellitus associated with arterial hypertension is major factor delivering lesion of target organs. Currently, enough data is not available about imaging and quantitative evaluations of arterial wall. There is no enough data available about the relations between MRI and inflammatory and metabolic markers in patients with resistant arterial hypertension concomitant with diabetes mellitus. AIMS: Quantitative assessment of the intensity of paramagnetic contrast enhancement of the arterial wall, in particular renal arteries walls, in relation with inflammatory and metabolic markers in patients with resistant arterial hypertension concomitant with diabetes mellitus. MATERIALS AND METHODS: The study groups were comprised of 28 patients (ageing 60,7±6,5 years) with resistant hypertension accompanied with diabetes mellitus and 17 patients (aging 57,7±5,0 years) with resistant hypertension without diabetes mellitus. The average systolic/diastolic pressure obtained from a 24-h monitor study was as high as 156,8±16,9/81,9,0±13,5 mm Hg in the group with diabetes and 154,8±11,9/88,5±10,4 mm Hg in the group without diabetes. The values of glycaemia, the level of glycated haemoglobin, and C-reactive protein were determined. The MRI studies were carried out using 1,5 Т MRI Toshiba Vantage Titan scanner. After that, the intravenous contrast enhancement has been carried out (with 0,5 М paramagnetic, as 0,2 ml/Kg). The index of enhancement (IE) was then calculated from these data, as a ratio of intensities of contrast-enhanced image to the initial nonenhanced MRI scan. RESULTS: The correlation was obtained for IE of arterial wall and data of blood pressure. Increased IE was correlated with ageing and hemodynamic factors. Also the correlation was observed for IE proximal, medium and distal parts of renal arteries and values of glycaemia and NOMA-index were obtained. Negatively correlated values for IE and adiponectin in the group with diabetes mellitus were obtained. The association between IE and C-reactive protein remained significant in the group without diabetes mellitus. CONCLUSIONS: MRI with contrast enhancement of arterial walls allows evaluating the anatomy of renal arteries and allows quantifying the pathophysiologic factors of their walls in patients with resistant hypertension accompanied with diabetes mellitus. MRI characteristics of the arterial wall were associated not only with hemodynamic and metabolic data, but also with markers of inflammation.